Zn composite corrosion resistance coatings: What works and what does not work?. (March 2021) - Anwar, Shams; Khan, Faisal; Zhang, Yahui; Caines, Susan
Abstract: Corrosion is one of the most significant contributors to structural degradation in process industries. It causes process equipment failure, which can led to severe safety issues. One approach to address this concern is to provide a preventive barrier-coating to equipment. Due to its superior reductive property, zinc is usually employed as a sacrificial anode in conventional corrosion-resistance methods. Nickel is also used to both mechanically strengthen the barrier and improve overall corrosion resistance; therefore, zinc, zinc-nickel alloys, and zinc-nickel-oxide composite coatings are commonly employed for anti-corrosion purposes. The complexation of zinc and nickel ions by agents (citrate, acetate and EDTA) can stabilize the electrodeposition bath and extend the pH of Ni(OH)2 and ZnO precipitation to improve corrosion resistance in the resultant coating. This paper reviews the challenge with these type of coatings and presents progress in Zn and Zn-Ni composite corrosion resistance coatings co-deposited with Al2 O3, TiO2, ZrO2, SiO2, and Fe2 O3 as means of corrosion control to reduce the probability of process equipment failure due to corrosion, which will improve the overall safety and reliability of processing equipment. Highlights: Reviews the challenge and present progress in the Zn and Zn-Ni composite corrosion resistance coating. Analyze the coating as means of corrosion control to reduce the probability of process equipment failure. Identifies the corrosion product that impacts kinetics of anodic or cathodic reactions and impact the coating's overall corrosion behaviour. Conclude Zn-Ni alloy coatings improve the overall safety and reliability of processing equipment.